The regulation of a project of the deregulation: UBER in Brazil and the European Union - Defossez, Delphine Aurélie Laurence (Journal of Law and Regulation, 2017)
Purpose ”“ This paper focuses on the regulation of Uber at regional level (Sao Paulo and Brasilia), national level (European Member States) and supranational level (The European Commission initiative), which are often too restrictive. Methodology/approach/design ”“ This article analyses standards and literature on regulation, as well as the role of competition. Attention was specially drawn to the market failure theory for justifying regulation, advocated by Breyer, Ogus and Baldwin & Cave. Due to the fact that there will be an evaluation of the regulations in place, consequentialism, welfarism and Pareto are briefly mentioned. Findings ”“ None of the current regulatory responses, at the exception to Sao Paulo and the initiative by the European Commission that are not based exclusively on market failure theory, are working. Indeed, Uber is still banned in various cities. In others, the regulatory burden is so high that it takes away any incentives that Uber created. Regulation is not the only exit to market failure, competition must play a role. Uber is based on deregulation of the market and to try to regulate such concept with conventional theories will only lead to failures and restrictions. Practical implications ”“ This article discusses the possible improvements to the already existing regulations. Originality/value ”“ This paper correlates the regulation of Uber in Brazil and in Europe, explaining the difficulties these regulations are creating for Uber.